Enhancement of RecET-mediated in vivo linear DNA assembly by a xonA mutation - James A. Sawitzke; Nina Costantino; Adriana Castillo Caballero; Ellen Hutchinson; Alessandro Barenghi; Lynn C. Thomason; Donald L. Court (PLoS ONE, 2026)
Assembly of intact, replicating plasmids from linear DNA fragments introduced into bacterial cells, i.e., in vivo cloning, is a facile genetic engineering technology that avoids many of the problems associated with standard in vitro cloning. Here, we report characterization of various parameters of in vivo linear DNA assembly mediated by either the RecET recombination system or the bacteriophage λ Red recombination system. As previously observed, RecET is superior to Red for this reaction when the terminal homology is 50 bases. Deletion of the E. coli xonA gene, encoding Exonuclease I, a 3’ → 5’ single-strand DNA exonuclease, substantially improves the efficiency of in vivo linear DNA assembly for both systems. Deletion of the Exonuclease I function allows robust RecET assembly of six DNA segments to create a functional plasmid. The linear DNAs are joined accurately with very few errors. This activity is at least as efficient and accurate as the NEBuilder® HiFi DNA Assembly in vitro method of assembling fragments. This discovery provides a significant improvement to previously reported in vivo linear DNA assembly technologies and provides a faster, less expensive, one-step method for assembling plasmids from multiple fragments.